Potential Carbon Content and Inorganic Carbon Sequestration in the Karst Area of Silokek Geopark, Sijunjung Regency - Pertiwi, Vera; Chairul, Chairul; Syamsuardi, Syamsuardi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Climate change caused by increasing greenhouse gas emissions, especially CO2, and deforestation, is an urgent global issue. The REDD+ program initiated by the UN aims to reduce carbon emissions and increase carbon storage in forests. One of the forests that can reserve carbon is the karst area with the ability to reserve carbon dioxide (CO2). This study aims to determine the potential carbon content and carbon dioxide (CO2) sequestration. This study was conducted using the chip sampling method and the XRF (X-ray Fluorescence) method analysis. Based on the research results, it is known that the Silokek Geopark karst area has three different limestone rock characteristics, and sample 3 is the type of rock with the highest CaO percentage. The potential inorganic carbon content is 4,908.07 tons/ha and carbon absorption is 18,012.60 tons/ha, categorized as high. The inorganic carbon content in the Silokek Geopark area is lower than the Biduk-biduk Karst area which is influenced by the area volume area and type of rock composition.